PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN CAPITAL INTENSITY TERHADAP PENGHINDARAN PAJAK - Monifa Yuliana Dwi Sandra; Achmad Syaiful Hidayat Anwar (Jurnal Akademi Akuntansi, 2018)
This study aims to investigate the effect of Corporate Social Responsibility (CSR) and Capital Intensity on the level of tax avoidance. This research is an associative study, with the population of mining companies listed on the IDX from 2015 to 2017. The samplig technique is Purposive sampling, and obtained a total sample of 48 companies. The data studied is the secondary data, which is then tested by Multiple Linear Regression analysis. The results demonstrate that the two variables have a significance value (p-value) < α 0.05, both in simultaneous and partial tests. CSR has a coefficient of -0.818, meanwhile, Capital intensity has a coefficient of 0.484. Therefore, it can be concluded that Corporate Social Responsibility (CSR) has a significantly negative effect on the tax avoidance. The higher the level of CSR disclosure, the lower the practice of tax avoidance. In addition, Capital intensity proved to have a significantly positive effect on the tax avoidance. The higher the company's capital intensity, the higher the tax avoidance practice.